Motivation of Parents to Send Their Children to Islamic Boarding Schools (Motivasi Orang Tua Menyekolahkan Anak di Pesantren) (Institut Agama Islam Negeri (IAIN) Kendari, 2023)
This article is to analyze: (1) the intrinsic motivation of parents in sending their children to Islamic boarding schools; (2) extrinsic motivation of parents in sending their children to Islamic boarding schools. This research was conducted qualitatively with a narrative approach. From the results of this research, the author can draw the following conclusions: The results of the research show that the intrinsic motivation of parents to send their children to Islamic boarding schools is because: (1) the desire to make their children pious and pious; (2) discipline; (3) not only having worldly knowledge but also mastering knowledge for the hereafter and obeying religious teachings; (4) forming noble morals, (5) preventing children from negative environmental impacts. The extrinsic motivation for parents to send their children to Islamic boarding schools is because: (1) Islamic boarding schools have more religious subjects, the influence of the surrounding environment is good and there are lots of positive activities every day, (2) The method of moral development is quite good. This research suggests that education is needed for parents to become more aware of the importance of sending their children to Islamic educational institutions with a dormitory system.Keywords: Intrinsic Motivation, Extrinsic Motivation, Islamic Boarding School